Conductive Education in Service of Pedagogical Rehabilitation of Persons With Motor Disabilities (Training and Practice : Journal of Educational Sciences, 2017)
In the case of children following a typical course of development the opportunities of pedagogy are widely known; what are, however, the opportunities in respect of the education and instruction of children with motor disabilities? Disability originating from damage to the central nervous system is one of the most frequently occurring conditions that need comprehensive rehabilitation. According to the current point of view in medicine, it cannot be cured but the residual symptoms may be reduced by development and education. Rehabilitation continues throughout the patient’s life and is provided by an established system of social and pedagogical institutions, inclusion, however, meets with difficulties even today. The present study treats conductive education as one of the possible implementations of pedagogical rehabilitation, highlighting the educational factors and effects that may ensure the preparation and at the same time the efficiency of inclusion.